Understanding the Airbnb user continuation intention: The moderating role of perceived risk - Zubair, Ahsan; Baharun, Rohaizat; Kiran, Faiqa; Abro, Muhammad Azeem (Frontiers in Psychology, 2022)
This study evaluates the relationship of diversified relationships established under the umbrella of the Stimuli-Organism-Response (SOR) framework to study the consumer continuation intention of the Airbnb platform from a Malaysian perspective. A web-based survey was conducted among Malaysian Airbnb consumers, and a sample of 303 respondents was obtained. SmartPLS has been used for data analysis. The statistical output of the respondent’s data indicates social overload and information overload influence consumer continuation intention. Moreover, the satisfaction and trust in platform partially mediate the relationship between the stimuli and behavioral response. Further, perceived health risk strengthens the negative relationship between continuation and trust in platform. Implications: The theoretical implications include enacting SOR framework to understand the consumer’s internal state of mind and ability to influence the consumer platform continuation intention. The practical implications make suggestion for the managers and business owners to focus on limiting the social exposure at the host destination and flow of information from the application.